Commitment devices: beyond the medical ethics of nudges - Hodson, Nathan (Journal of medical ethics, 2023)
Commitment devices (CDs) can help people overcome self-control problems to act on their plans and preferences. In these arrangements, people willingly make one of their options worse in order to change their own future behaviour, often by setting aside a sum of money that they will forfeit it if they fail to complete the planned action. Such applications of behavioural science have been used to help people stick to healthier lifestyle choices, overcome addictions and adhere to medication; they are acceptable to many patients and even relatively small sums can be effective. Some authors have objected to the use of nudges in healthcare. Engelen has listed nine potential objections to nudges in relation to means (why nudge rather than persuade?), ends (what action is being promoted?) and agents (who is nudging whom?). These objections are shown to lack force in the context of CDs. Instead, an analysis specific to the ethical issues in CDs is employed. CDs exclude certain groups including so-called ‘naifs’ and risk increasing health inequality. CDs may promote the wrong behaviour and people might legitimately change their minds. Intermediaries might encounter perverse incentives. Approaches to overcoming these problems are described and eight key ethical considerations for those considering implementing CDs in the future are described. Altogether this paper illustrates the advantages of appraising the ethics of behavioural science in medicine on a case-by-case basis.